EKSPLORASI ETNOMATEMATIKA PERMAINAN ULAR TANGGA PADA PEMBELAJARAN MATEMATIKA - Nor Nadia; Hasan Basri; Wildona Zumam; Rohmawati, Indah; Thariq Fajrih Rahman; Intan Dwi Noer Aini (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
The specific objective of this study is to reveal and describe the ethnomathematical elements found in the traditional game of snakes and ladders. This study uses a qualitative approach that links mathematical concepts to the local cultural context. Data analysis in this study was carried out in three main stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of the observation, it was found that the traditional game of snakes and ladders contains various ethnomathematical elements that can be utilized in mathematics learning. These elements arise naturally during the game according to the applicable rules. The traditional game of snakes and ladders contains various mathematical concepts, such as numbers, geometry, probability, and game rules that reflect mathematical activities.